2004
DOI: 10.1074/jbc.m402528200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Functionally Important Elements in the Multidrug Resistance Protein 1 COOH-terminal Region

Abstract: The ATP binding cassette (ABC) transporter, multidrug resistance protein 1 (MRP1/ABCC1), transports a broad spectrum of conjugated and unconjugated compounds, including natural product chemotherapeutic agents. In this study, we have investigated the importance of the COOH-terminal region of MRP1 for transport activity and basolateral plasma membrane trafficking. The COOH-terminal regions of some ABCC proteins have been implicated in protein trafficking, but the function of this region of MRP1 has not been defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 60 publications
2
24
0
Order By: Relevance
“…The results obtained with MRP1 204 -1531 -YFP suggested that elements that contributed to targeting of the MRP1 core to the plasma membrane might be located in the COOH-terminal region of the protein. However, we found recently that up to 30 amino acids could be removed from the COOH terminus of full-length MRP1 without affecting trafficking, despite the fact that removal of only four amino acids was sufficient to markedly decrease transport activity (Westlake et al, 2004). As observed previously, subcellular localization of MRP1 1-1501 and MRP1 1-1527 was indistinguishable from that of the full-length protein ( Figure 6, A and B).…”
Section: Mrp1 204 -1531 -Cfp Colocalizes With Internalized Transferrinsupporting
confidence: 58%
See 4 more Smart Citations
“…The results obtained with MRP1 204 -1531 -YFP suggested that elements that contributed to targeting of the MRP1 core to the plasma membrane might be located in the COOH-terminal region of the protein. However, we found recently that up to 30 amino acids could be removed from the COOH terminus of full-length MRP1 without affecting trafficking, despite the fact that removal of only four amino acids was sufficient to markedly decrease transport activity (Westlake et al, 2004). As observed previously, subcellular localization of MRP1 1-1501 and MRP1 1-1527 was indistinguishable from that of the full-length protein ( Figure 6, A and B).…”
Section: Mrp1 204 -1531 -Cfp Colocalizes With Internalized Transferrinsupporting
confidence: 58%
“…In contrast, processing and trafficking of SUR1A and MRP2 is impaired after removal of only the COOH-terminal seven and 15 amino acids, respectively (Sharma et al, 1999;Nies et al, 2002). The different effects of COOH-terminal truncation of MRP1 and MRP2 was unexpected because substitution of COOH-terminal region of MRP1 with that of MRP2 had no effect on trafficking (Konno et al, 2003;Westlake et al, 2004), even in the absence of MSD0 (Figure 8A), suggesting a high level of functional conservation between the COOH-terminal regions of the two MRPs.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations